1994
DOI: 10.1091/mbc.5.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of native and reassembled neurofilaments composed of NF-L, NF-M, and NF-H by the catalytic subunit of cAMP-dependent protein kinase.

Abstract: native NF was nearly the same as that of purified NF-L. However, phosphorylation did not cause the native NFs to disassemble into oligomers, as was the case for purified NF-L. Instead, partial fragmentation was detected in sedimentation experiments and by electron microscopic observations. This is probably not due to the presence of the three NF subunits in NF or to differences in phosphorylation sites because reassembled NF containing all three NF subunits were disassembled into oligomeric forms by phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 52 publications
4
51
0
Order By: Relevance
“…Although the NF subunits and their relevant kinases are synthesized in cell bodies, stable phosphorylation of most KSP repeats in the NF-M and NF-H C-terminal tail domains by proline-directed kinases occurs primarily in the axon during slow transport (7, 16, 50 -53). On the other hand, phosphorylation of N-terminal head domain motifs by PKA and PKC occurs transiently in cell bodies and prevents NF assembly (3,4,9,10,12,19,21,55). If this occurs immediately after synthesis, premature cell body assembly is inhibited thereby protecting the neuron from abnormal accumulations of phosphorylated cytoskeletal aggregates, as seen in such neurodegenerative disorders as ALS (56).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the NF subunits and their relevant kinases are synthesized in cell bodies, stable phosphorylation of most KSP repeats in the NF-M and NF-H C-terminal tail domains by proline-directed kinases occurs primarily in the axon during slow transport (7, 16, 50 -53). On the other hand, phosphorylation of N-terminal head domain motifs by PKA and PKC occurs transiently in cell bodies and prevents NF assembly (3,4,9,10,12,19,21,55). If this occurs immediately after synthesis, premature cell body assembly is inhibited thereby protecting the neuron from abnormal accumulations of phosphorylated cytoskeletal aggregates, as seen in such neurodegenerative disorders as ALS (56).…”
Section: Discussionmentioning
confidence: 99%
“…N-terminal head domain phosphorylation by PKA at Ser 55 in NFL or Ser 46 in NF-M inhibits assembly into a heteropolymer in vitro and in vivo (3,9,12,19,20). It has been suggested that this transient head domain phosphorylation in cell bodies inhibits NF polymerization and filament formation (4,21).…”
Section: Neurofilament (Nf)mentioning
confidence: 99%
“…Comparison of two-dimensional peptide maps of NF-L from optic axons of mice intravitreally injected with 32 P with those from in vitro labeled NF-L has been used to characterize serine 55 as an in vivo phosphorylation site on NF-L (30). This involved HPLC purification and subsequent Edman degradation of a phosphopeptide common to both samples followed by in vitro phosphorylation and sequencing of a corresponding synthetic peptide to locate the exact site of phosphorylation.…”
mentioning
confidence: 99%
“…Recent studies show that phosphorylation also plays a critical role in inhibiting NF assembly in the perikaryon, which explains why NFPs only form filaments in axons [15,62,67]. N-terminal head domain phosphorylation by protein kinase A (PKA) at Ser 55 in NF-L or Ser 46 in NF-M inhibits assembly of NF subunits into a heteropolymer in vitro and in vivo [78][79][80][81][82]. Consistent with these studies, phosphorylation/dephosphorylation of Ser 55 and Ser 57 in NF-L regulates NF assembly and disassembly [83,84].…”
Section: Phosphorylationmentioning
confidence: 99%
“…These findings are consistent with the hypothesis that transient phosphorylation of NF-M head domains inhibits phosphorylation of tail domains and poses a new mechanism for topographic regulation of NFP phosphorylation in neurons. So transient phosphorylation of head domain motifs of NF-L and NF-M by PKA and PKC in cell bodies can prevent NF assembly and C-terminal phosphorylation in perikarya [22,78,80,81,85], protecting the neuron from abnormal accumulation of phosphorylated NFP aggregates in cell bodies. In fact, few NFs are seen in cell bodies, and only small oligomers can be detected, which suggests that consequential NF assembly is restricted to axons during transport [87].…”
Section: Phosphorylationmentioning
confidence: 99%